2016
DOI: 10.1515/sg-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca2+ on in vitro pollen germination of three Acacia species

Abstract: We investigated the effects of Ca . With high Ca 2+ concentration, the pollen germination of A. auriculiformis, A. mangium, and A. crassicarpa were obviously inhibited. With the rise of Ca 2+ concentration, the percentage of pollen germination, the pollen tube length, the pollen tube growth, and the number of pollen tube were increased. However, the pollen germination percentage decreased with high Ca 2+ concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Studies have shown that when SI occurs, the increase in the Ca 2+ concentration leads to the inhibition of pollen tube growth [13,65], and the increase in Ca 2+ is related to the SI response [66,68]. A study of A. mangium showed that high concentrations of Ca 2+ exert a significant inhibitory effect on pollen germination [69]. Our study also identified 28 calcium-dependent protein kinase genes that were significantly differentially expressed.…”
Section: Transcriptomic Analysismentioning
confidence: 51%
See 3 more Smart Citations
“…Studies have shown that when SI occurs, the increase in the Ca 2+ concentration leads to the inhibition of pollen tube growth [13,65], and the increase in Ca 2+ is related to the SI response [66,68]. A study of A. mangium showed that high concentrations of Ca 2+ exert a significant inhibitory effect on pollen germination [69]. Our study also identified 28 calcium-dependent protein kinase genes that were significantly differentially expressed.…”
Section: Transcriptomic Analysismentioning
confidence: 51%
“…Our previous research on the pollen vitality of A. mangium has proven the vitality of fresh pollen [44]. Less than 6.67% of polyad-pistil combinations resulted in the germination of the grains after self-pollination or hand-controlled cross-pollination (Table S1), and others (over 90% of the pollen grains) produced no pollen tube growth on the stigma/style (Table S1, Figure 1A).…”
Section: Microscopy Observation Of Pollen Germination and Stigma Cont...mentioning
confidence: 91%
See 2 more Smart Citations